2022
DOI: 10.1021/acssuschemeng.2c00449
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transition in Cobalt Selenide with a Greatly Improved Electrocatalytic Activity in Hydrogen Evolution Reactions

Abstract: Surface properties such as electronic structures and valence state determine the electrocatalytic activity in hydrogen evolution reactions (HERs). Herein, we prepared a novel orthorhombic CoSe 2 -NC (o-CoSe 2 -NC) electrocatalyst from hexagonal CoSe-NC (h-CoSe-NC) via a phase-transition method. As-prepared o-CoSe 2 -NC exhibited excellent HER activity with 147 mV at 10 mA cm −2 and a high stability (24 h). Density functional theory results revealed that the active sites for h-CoSe-NC in electrocatalytic hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…46 Temperature-optimized CoS 1.097 -160 had a lower Tafel slope (53 mV dec −1 ), which demonstrated faster surface kinetics resulting in improved HER performance. 47,48 The calculated Tafel slope (in mV dec −1 ) was lower than that of the other as-prepared products, such as CoS 1.097 -140 (64), CoS 1.097 -180 (69), and bare CoS X (77). Furthermore, the Tafel slope of precious Pt/C (31 mV dec −1 ) was used to compare the Tafel slope of the as-prepared non-precious cobalt sulfide products (Fig.…”
Section: Resultsmentioning
confidence: 83%
“…46 Temperature-optimized CoS 1.097 -160 had a lower Tafel slope (53 mV dec −1 ), which demonstrated faster surface kinetics resulting in improved HER performance. 47,48 The calculated Tafel slope (in mV dec −1 ) was lower than that of the other as-prepared products, such as CoS 1.097 -140 (64), CoS 1.097 -180 (69), and bare CoS X (77). Furthermore, the Tafel slope of precious Pt/C (31 mV dec −1 ) was used to compare the Tafel slope of the as-prepared non-precious cobalt sulfide products (Fig.…”
Section: Resultsmentioning
confidence: 83%
“…The surface electronic state of CoSe, MoSe 2 , and CoSe/MoSe 2 was characterized by X-ray photoelectron spectroscopy (XPS). Figure S7 shows that the presence of Co, Mo, and Se elements in CoSe/MoSe 2 electrocatalysts and the presence of O elements in the electrocatalyst may be caused by oxidation. , As shown in Figure d, Co 3+ resulted in peaks at 778.33 and 793.31 eV. Also, Co 2+ exhibited peaks at 780.55 and 796.58 eV, respectively .…”
Section: Resultsmentioning
confidence: 93%
“…Typically, phase transition of TMSes is direct method for enhancing the electrocatalytic activity. 107 In the study of Zhao et al, 3D electrode with controllable charge state (Co 3+ /Co 2+ ) was reported by reasonable turning the relative content of Se powder and Co foil, wherein Co 3+ /Co 2+ was favorable to the OER/-HER, respectively, on the basis of synchrotron-based mechanism study. 45 Such sample was successfully constructed with the combination of CoSe and Co 9 Se 8 phases, which played an important role in seawater electrolysis due to the specific electronic structure.…”
Section: Transition Metal Dichalcogenidementioning
confidence: 99%
“…Though TMSes exhibit excellent properties for seawater splitting, it is suffered from many issues such as poor conductivity and the lack of exposed active sites, which need to be addressed with proper strategies in the near future. Typically, phase transition of TMSes is direct method for enhancing the electrocatalytic activity 107 . In the study of Zhao et al, 3D electrode with controllable charge state (Co 3+ /Co 2+ ) was reported by reasonable turning the relative content of Se powder and Co foil, wherein Co 3+ /Co 2+ was favorable to the OER/HER, respectively, on the basis of synchrotron‐based mechanism study 45 .…”
Section: Tm‐based Electrocatalysts For Driving Seawater Electrolysismentioning
confidence: 99%